Clergy as a frontline mental health service: a UK survey of medical practitioners and clergy. Issue 6 (23rd October 2020) - Heseltine-Carp, William; Hoskins, Mathew
Abstract : Background: Christian clergy have often been identified as 'frontline mental health workers' and gatekeepers to mental health services. However, despite this, collaboration between clergy and mental health services remains poor, with some US clergy referring on as little as 10% of cases. Aims: In this study, we aimed to evaluate the collaborative relationship between UK clergy and medical practitioners, with the purpose of identifying key issues that should be addressed to improve such collaboration between the two services. Methods: We surveyed 124 clergy, 48 general practitioners and 13 psychiatrists in Wales. Part 1 of the survey covered four main themes: demographics; types of mental health cases seen by clergy and practitioners; referral rates between clergy and mental health services; attitude and relationship between clergy and mental health services. Part 2 was directed at clergy only and assessed how sensitive clergy were in identifying and referring on mental health disorders by using seven virtual case vignettes. Results: Clergy frequently encountered mental health cases and around 60%–80% regularly referred on to a healthcare professional. Clergy appeared very effective at identifying and referring on high risk scenarios, such as psychosis, suicidal ideation and substance misuse, however were less effective at identifying and referring on clinical depression and anxiety. Clergy rarely received referrals from medical professionals. Both medical professionals and clergy felt they needed to engage in a more collaborative relationship, and around of one-third of practitioners were prepared to offer training to clergy. Conclusion: Most clergy in Wales regularly encounter mental health cases and appear effective at recognising and referring on mental health disorders; however, a large minority do not (20%–40%). Clergy generally do not receive referrals from mental health professionals, despite the proven benefits. Therefore, improving collaboration, developing spiritual training for mental health professionals, and mental health training for clergy is likely useful, a notion that many clergy and medical professionals deem important and are prepared to support.